2020
DOI: 10.3390/molecules25143180
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Anti-Tumor Activity of Novel Benzimidazole-Chalcone Hybrids as Non-Intercalative Topoisomerase II Catalytic Inhibitors

Abstract: Chemical diversification of type II topoisomerase (Topo II) inhibitors remains indispensable to extend their anti-tumor therapeutic values which are limited by their side effects. Herein, we designed and synthesized a novel series of benzimidazole-chalcone hybrids (BCHs). These BCHs showed good inhibitory effect in the Topo II mediated DNA relaxation assay and anti-proliferative effect in 4 tumor cell lines. 4d and 4n were the most potent, with IC50 values less than 5 μM, superior to etoposide. Mechanistic stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Chalcones have been shown to exhibit anticancer activity through their inhibitory potential against various targets, such as 5α-reductase [ 187 ], aromatase [ 188 ], histone deacetylase inhibitors (HDAC) [ 189 , 190 ], proteasome [ 191 , 192 ], JAK/STAT signaling pathways [ 193 ], cell division cycle 25 (CD25) [ 194 ], cathepsin-K [ 72 , 195 ], topoisomerase-II [ 196 , 197 ], Wnt [ 198 , 199 ], ROS/MAPK [ 200 ], p38 [ 201 , 202 ] and mTOR [ 203 , 204 ]. However, these studies are not covered in this review because not enough evidence has been provided to indicate that these proteins or pathways are direct targets of chalcones.…”
Section: Representative Mechanisms Of Anticancer Action Of Chalconesmentioning
confidence: 99%
“…Chalcones have been shown to exhibit anticancer activity through their inhibitory potential against various targets, such as 5α-reductase [ 187 ], aromatase [ 188 ], histone deacetylase inhibitors (HDAC) [ 189 , 190 ], proteasome [ 191 , 192 ], JAK/STAT signaling pathways [ 193 ], cell division cycle 25 (CD25) [ 194 ], cathepsin-K [ 72 , 195 ], topoisomerase-II [ 196 , 197 ], Wnt [ 198 , 199 ], ROS/MAPK [ 200 ], p38 [ 201 , 202 ] and mTOR [ 203 , 204 ]. However, these studies are not covered in this review because not enough evidence has been provided to indicate that these proteins or pathways are direct targets of chalcones.…”
Section: Representative Mechanisms Of Anticancer Action Of Chalconesmentioning
confidence: 99%
“…Further biological evaluation of these compounds showed that they induced apoptosis and inhibited human topoisomerase II α as a possible intracellular target. Zhou et al (2020) designed and synthesized a novel series of benzimidazole-chalcone hybrids (BCHs). These BCHS showed good inhibition in the Topo II-mediated DNA relaxation assay and good anti-proliferative effects in four tumor cell lines (A549, HePG-2, MG63, LNCaP), with 4h and 4i being the most potent with IC50 values <5 µM, superior to Etoposide.…”
Section: Dna Topoisomerase Inhibitorsmentioning
confidence: 99%
“…Chalcones occur in the cis or trans form, of which the trans isomer is more thermodynamically stable than the cis form. Chalcones have been reported to have biological properties such as anticancer [ 3 ] antimicrobial [ 4 ], antiviral [ 5 ], antioxidant [ 6 ], anti-Alzheimer’s [ 7 ], antitumor [ 8 ], antidiabetic [ 9 ], anti-Parkinson’s [ 10 ], anti-inflammatory [ 11 ], and anti-nociceptive [ 12 ] effects ( Figure 1 ). After a careful literature search, it has been found that in the past decade many scientific developments took place in chalcone chemistry, which is scattered in nature.…”
Section: Introductionmentioning
confidence: 99%